Analisis Kolam Retensi Sebagai Pengendalian Banjir Genangan Di Kecamatan Payung Sekaki - Desyi Astuti; Siswanto Siswanto; Imam Suprayogi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The problems that occurred in the city of Pekanbaru precisely in the District Payung Sekaki Area that AKAP terminal road Bandar Raya Payung Sekaki namely flood inundation. Construction of retention ponds is one of the strategic measures that could be considered in an effort to control flooding in the city of Pekanbaru. From the calculation of flood discharge plan using Rational Method obtained flood discharge plan that is equal to 20,482 m3/s. Areas of study is divided into 9 subcathment which in total was 108,313 ha. From the analysis using EPA SWMM 5.0 obtained capacity retention pond is 18.000 m3 while the total volume of the incoming flood retention pond in the amount of 272.082,89 m3 thus the effectiveness of retention ponds to control floods in the amount of 7,35% with a return period of 25 years of planning.Keywords: flood discharge, retention ponds, flood control